2016
DOI: 10.1159/000450889
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and Time-Dependent Cellular Effects of Cold Atmospheric Pressure Plasma Evaluated in 3D Skin Models

Abstract: Background: Application of cold atmospheric pressure plasmas (CAPs) in or on the human body was termed ‘plasma medicine'. So far, plasmas were utilized for sterilization of implants, other heat-sensitive products, or employed for chemical surface modifications. By now, CAPs are further used effectively for wound treatment. The present study analyses the effect of a plasma jet with air or nitrogen as process gas, previously evaluated for antimicrobial efficacy, on human cells using a 3D skin model. Methods: CAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
1
27
0
2
Order By: Relevance
“…[28] Cytokines and chemokines are the major regulators of inflammation in wound healing. [30] Similarly, Arndt reported that 2 min CAP treatment (microwave 2.45 GHz, 110 W, argon flow rate 4.0 L/min, treatment diameter 5 cm) increased the expression of some key genes of pro-inflammatory factors, such as IL-6, IL-8, MCP-1, TGF-1, and TGF-2, and improved wound healing. [20] Wiegand et al found that when CAP with air or nitrogen as the process gas is used, an increase in the expression of IL-6 and IL-8 (pro-inflammatory factor) occurred in a power-dependent (100-300 W) and time-dependent (5-15 s) manner in 3D skin models.…”
Section: Discussionmentioning
confidence: 94%
“…[28] Cytokines and chemokines are the major regulators of inflammation in wound healing. [30] Similarly, Arndt reported that 2 min CAP treatment (microwave 2.45 GHz, 110 W, argon flow rate 4.0 L/min, treatment diameter 5 cm) increased the expression of some key genes of pro-inflammatory factors, such as IL-6, IL-8, MCP-1, TGF-1, and TGF-2, and improved wound healing. [20] Wiegand et al found that when CAP with air or nitrogen as the process gas is used, an increase in the expression of IL-6 and IL-8 (pro-inflammatory factor) occurred in a power-dependent (100-300 W) and time-dependent (5-15 s) manner in 3D skin models.…”
Section: Discussionmentioning
confidence: 94%
“…By using a basic infection model, this pilot study provides a closer insight of pathogen–host interactions and the involvement of non‐professional cutaneous immune cells participating in the defence against the DSM 6916 strain of T. benhamiae . Follow‐up studies will use an infection model employing a human collagen‐based skin model that comprises fibroblasts building a dermis and keratinocytes generating the different strati of a human epidermis …”
Section: Discussionmentioning
confidence: 99%
“…Followup studies will use an infection model employing a human collagen-based skin model that comprises fibroblasts building a dermis and keratinocytes generating the different strati of a human epidermis. 65…”
Section: Discussionmentioning
confidence: 99%
“…The microbicidal effect of CAP was observed in vitro [256,257,258,259,260,261] on skin and chronic wounds, and exceeds the effectiveness of CHD, PVP-I, and PHMB. In a 3D epidermis model, CAP displayed dose- and time-dependent compatibility [256]; P. aeruginosa was inactivated without destroying the structure of the epidermis.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In a 3D epidermis model, CAP displayed dose- and time-dependent compatibility [256]; P. aeruginosa was inactivated without destroying the structure of the epidermis. Cell proliferation is supported in cell culture [247].…”
Section: Future Perspectivesmentioning
confidence: 99%